Writing of Rajni Kothari (New Delhi, 2009)
This volume brings together three landmark books- Politics in India, Caste in Indian Politics and Rethinking Democracy. Drawing upon contributions from various disciplines, Politics in India is the first comprehensive treatment of the Indian political system examined from different vantage points.
Keywords: Indian politics